Consumption and Digestibility Studies in Goats Fed with Complete Feed Corn Tumpi and Red Dragon Fruit Peel Flour (Hylocereus Sp.) - Mariam, Mariam; Natsir, Asmuddin; Syahrir, Syahriani (Hasanuddin Journal of Animal Science (HAJAS), 2023)
Utilization of unconventional materials such as corn tumpi and dragon fruit peel flour as an alternative feed ingredient for ruminants, especially goats. This study aims to examine the effect of providing complete feed containing corn tumpi with dragon fruit peel flour at different levels on consumption and digestibility of goats. This study used 12 local male goats with ages ranging from 1 to 1.5 years which were randomly assigned to metabolic cages. The study used a Randomized Block Design (RBD) method with 3 treatments and 4 groups. The treatments consisted of P1: Complete feed containing 50% corn tumpi, P2: Complete feed containing 45% corn tumpi and 5% dragon fruit peel flour and P3: Complete feed containing 40% corn tumpi and 10% dragon fruit peel flour. The results showed that the treatment of complete feed containing corn tumpi with dragon fruit peel flour at different levels had a significant effect (P<0.05) on dry matter consumption and organic matter consumption. Dry matter consumption ranged from 296.88 – 461.64 g/h/day, and nitrogen consumption was between 265.74 – 407.72 g/h/day. Treatment of complete feed containing corn tumpi with dragon fruit peel flour at different levels had no significant effect (P>0.05) on dry matter digestibility and organic matter digestibility. Dry matter digestibility ranged from 82.75 – 87.50 %, and organic matter digestibility between 84.5 – 88.75 %. It was concluded that based on estimates of dry matter consumption and organic matter consumption, the use of alternative ingredients for corn tumpi with dragon fruit peel flour up to a level of 10% could be used as a complete mix of feed ingredients for ruminants, especially goats.